The 200 most influential publications in migraine research: a bibliometric mapping of the intellectual landscape - Chen, Qianxiu; Wei, Shijie; Jiang, Guoliang; Hu, Xiaowei; Zhang, Lili; Li, Pengcheng; Han, Jing (Frontiers in Neurology, 2025)
BackgroundMigraine is a prevalent and highly disabling neurological disorder. A systematic evaluation of its foundational literature is essential for advancing management strategies. This study employed bibliometric methods to trace the historical trajectory of migraine research and identify principal developmental trends.MethodsThe Web of Science and PubMed database was searched to identify the 200 most highly cited publications, filtered by date, language, and document type. Comprehensive analyses and visualizations were conducted using bibliometrix (R), VOSviewer, Scimago Graphica, CiteSpace, and Microsoft Excel.ResultsThe selected publications appeared in 45 journals across 45 countries, authored by 4,409 researchers from 1,592 institutions. Together, these works incorporated 860 keywords and cited 7,995 references. Neurology, Cephalalgia, and Headache were the leading journals, while Lipton RB and Goadsby PJ were the most influential authors. The United States led in publication volume, with Albert Einstein College of Medicine among the top institutions. Ten landmark papers were highlighted, and their contributions, along with those of the broader corpus, were systematically reviewed. Key research hotspots were also delineated.ConclusionCurrent high-impact research emphasizes treatment, therapeutic targets, genetics, the trigeminovascular system, pain modulation, neuroimmunology, aura, and comorbidities. Recent studies confirm sustained interest in these areas, with increasing focus on the brain–gut axis. Future directions include deeper investigation of migraine pathophysiology, especially the calcitonin gene-related peptide system and episodic migraine subtypes. Rigorous methodologies and emerging technologies will enhance evidence-based evaluations of long-term safety and efficacy, while multidimensional assessments of pharmacological and non-pharmacological therapies are expected to expand.